Responses of Dwarf Chameleons to global change drivers - Clark, Tyron (My University, 2019)
Habitat loss, driven by climate and land use change, poses one of the greatest threats to biodiversity worldwide. Together these global change drivers are expected to act not only additively but synergistically in their impacts on biodiversity. Despite this, few studies address both aspects simultaneously. Nowhere are these threats more pertinent than in areas of high species richness and endemicity where there are high levels of anthropogenic pressure. The dwarf chameleons (Bradypodion) of KwaZulu-Natal Province, South Africa (KZN), provide one such case. The province is rapidly developing and is subject to high rates of habitat loss, a threat which is likely to be exacerbated by climate change in the future. Such rapid rates of change are expected to challenge the persistence of the province’s rich dwarf chameleon assemblage in the near future. Anticipating the responses of dwarf chameleons to these global change drivers and identifying traits which may infer higher vulnerability is critical to their effective protection especially as pressure mounts on conservationists to prioritise efforts and resources more discerningly. Recent advances in niche modelling techniques, global climatic change data and the production of a time series set of high resolution, directly comparable satellite derived land cover layers for KZN provided an opportunity to explore the potential effects of these global change drivers on this imperilled group of reptiles. Current ecological niche models (ENMs) were constructed for all nine Bradypodion species in KZN using a combination of fine-scale, bioclimatic variables and these land-cover datasets. These ENMs were then projected under scenarios of future climate (under five global circulation models for two atmospheric greenhouse gas concentrations) and land use change (using a simple yet intuitive habitat transformation rule based on published trends for the province). The findings suggest that KZN dwarf chameleon species are likely to respond individualistically to the effects of climate and land use change. Under an assumption of unlimited dispersal ability, a distinction can be made in the modelled responses of KZN dwarf chameleons to future climate change. Specifically, between inland species, whose responses are marked by contractions in climatically suitable natural habitat (CSNH), and more coastal species characterised by a maintenance or expansion in their extent of future CSNH. It was subsequently found that these groups and the gradient of susceptibility contained within them was better explained by niche preference and the future availability of a specific set of climatic conditions (variables) typically associated with a species’ occurrence than it was by range size or niche breadth. However, under more restrictive (and perhaps more realistic) assumptions incorporating dispersal ability showed notable contractions regardless of climatic resilience. Particularly concerning in this regard, is that most of the study species showed a reduction in the extent of CSNH predicted to coincide with the provinces protected area network in future. At present, the conservation status of KZN’s dwarf chameleons does not adequately reflect their anticipated susceptibility to these change drivers nor the extent of CSNH that is predicted to remain under statutory protection. These findings highlight the importance of upholding and pre-emptively expanding the provinces protected areas network to keep pace with the impending changes.
A Dissertation submitted to the School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, South Africa in fulfillment of the requirements of the degree of Master of Science. May 2019